Resonant switched-mode DC-DC converters - Maretta Shilviani Kumara (2014)
Soft-switching (resonant) switched-mode DC-DC converters can have potential advantages, such as lower overshoot, switching and conduction losses, and electromagnetic interference, compared to their standard hard-switching counterparts. This report reviews and investigates two types of resonant-based switched-mode DC-DC converters: Zero Current Switching (ZCS) and Zero Voltage Switching (ZVS). The operation principle of ZCS is zero current during the turn-off transition. The operation principle of ZVS is zero voltage during the turn-on transition. Generally, ZVS is more advantageous than ZCS due to the ability to eliminate overvoltage, switching loss, and electromagnetic interference. In this report, we investigate ZVS for low-power applications.